Organizations, Diffused Pivotality and Immoral Outcomes - Armin Falk; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies how organizational design affects moral outcomes. Subjects face the decision to either kill mice for money or to save mice. We compare a Baseline treatment where subjects are fully pivotal to a Diffused-Pivotality treatment where subjects simultaneously choose in groups of eight. In the latter condition eight mice are killed if at least one subject opts for killing. The fraction of subjects deciding to kill is higher when pivotality is diffused. The likelihood of killing is monotone in subjective perceptions of pivotality. On an aggregate level many more mice are killed in Diffused-Pivotality than Baseline.
Keywords: C91; D01; D03; D23; D63; 330; morality; pivotality; experiment; organization